Exploiting a natural instance of vertebrate-posed chemical aposematism for tick bite prevention: Repellency of Ixodes scapularis with (E)-Oct-2-enal - Eric L. Siegel; Sophia Goodnow; Lucy Thompson; Sarah Nicolson; Elizabeth MacLeod; Andrew Y. Li; Guang Xu; Stephen M. Rich (PLoS ONE, 2025)
Ticks are medically important, nuisance arthropods found worldwide. Applications of semiochemical-based tick repellents for personal protection and reproductive/reservoir host-targeted tick interventions are understudied. We evaluated the repellency of a semiochemical allomone of donkey sebum, (E)-oct-2-enal, against adult Ixodes scapularis ticks – the most frequent human-biting tick in the United States. Ticks were exposed to 20% solutions of (E)-oct-2-enal or DEET. A filter paper bioassay was applied under laboratory conditions. Behaviour was observed for 10-min and captured with a tracking software. Changes in velocity and peregrination were assessed relative to negative (ethanol) control groups using multivariable robust regression models. Repellent longevity was defined by preventing ticks from crossing the treated surface and was evaluated as time-to-event data with a Cox proportional hazard regression model. Significant reductions in velocity, increases in peregrination, and strong longevity were observed for both repellents. Overall assessment of repellency indexes with a Principal Component Analysis showed that DEET and (E)-oct-2-enal were more effective against male ticks than female ticks. There was no difference in effect on females for each repellent. However, the repellency index for male ticks exposed to (E)-oct-2-enal was significantly greater than DEET. This represents the first report, to our knowledge, of the repellency of a natural, vertebrate-emitted semiochemical against I. scapularis ticks. Work is needed to understand the underlying mechanism of action of semiochemical repellents. The development of (E)-oct-2-enal formulations for practical use in personal protection or reproductive/reservoir host-targeted tick control products warrants further consideration.